Prevalence and clinical implications of interactive toxicity beliefs regarding mixing alcohol and antiretroviral therapies among people living with HIV/AIDS. - Kalichman, Seth C; Amaral, Christina M; White, Denise; Swetsze, Connie; Pope, Howard; Kalichman, Moira O; Cherry, Chauncey; Eaton, Lisa (AIDS patient care and STDs, 2009)
Alcohol use is a barrier to medication adherence. Beyond the cognitive effects of intoxication, people living with HIV/AIDS who believe that alcohol should not be mixed with their medications may temporarily stop taking medications when drinking. To examine the effects of alcohol-treatment beliefs on HIV treatment adherence. People living with HIV/AIDS who were receiving treatment (n = 145) were recruited from community and clinical services during the period between January 2006 and May 2008 to complete measures of substance use and alcohol-antiretroviral (ARV) interactive toxicity beliefs (e.g., alcohol breaks down HIV medications so they will not work). Medication adherence was monitored using unannounced telephone-based pill counts. Forty percent of participants were currently using alcohol and nearly one in four drinkers reported stopping their medications when drinking. Beliefs that mixing alcohol and medications is toxic were common among drinkers and nondrinkers, with most beliefs endorsed more frequently by non-drinkers. Hierarchical regression analysis showed that stopping ARVs when drinking was associated with treatment nonadherence over and above quantity/frequency of alcohol use and problem drinking. Beliefs that alcohol and ARVs should not be mixed and that treatments should be interrupted when drinking are common among people living with HIV/AIDS. Clinicians should educate patients about the necessity of continuing to take ARV medications without interruption even if they are drinking alcohol.
Keywords: Alcohol Drinking; Anti-HIV Agents; Attitude to Health; Drug Interactions; Female; HIV Infections; Humans; Male; Medication Adherence; Prevalence; Regression Analysis; Socioeconomic Factors